Challenges in managing micro enterprise : a case of 1AZAM 1MALAYSIA social entrepreneurship program - Ab-Rahman; Symeon Mandrinos; Hashim (Faculty of Entrepreneurship and Business,UMK, 2015)
The objective of this paper is to reveal the finding of the research that explores the challenges of managing a micro enterprise. Previous studies have explored the challenges encountered and had found several challenges such as competition among themselves and also from large firms, lack of access to credit, cheap imports, insecurity and debt collection. However, previous studies on the challenges and strategies encountered emerge from the knowledge of actors from small and medium enterprise. Whereas the characteristic and the interaction happened within micro business and small business are different. Therefore, this study focuses on micro business only. This study utilises a qualitative research method. The participants in this research are the entrepreneurs that involve in 1AZAM 1MALAYSIA social entrepreneurship program. 5 participants are involved in this research. The data source is interview using in-depth interview technique. The duration of interview is approximately 45 minutes. The analysis used is thematic analysis. It is found that individual, the external environment and institution are the challenges’ factors faced by the entrepreneurs in micro business. Future research should use this study finding for statistical generalisation.